Expression of vascular endothelial factor protein in the tumor tissues of patients with Stages I-II ovarian cancer - V. L. Karapetyan; E. V. Stepanova; A. Yu. Baryshnikov; S. O. Nikogosyan; V. V. Kuznetsov; T. Sh. Tagibova (Опухоли женской репродуктивной системы, 2014)
To define tumor markers is presently the most interesting and promising direction for the diagnosis of malignancies. The expression of the major angiogenesis factor vascular endothelial growth factor (VEGF) in primary tumor tissue was studied in ovarian cancer (OC) patients to define the prognostic value of the marker.The study enrolled 48 patients with OC. The immunohistochemical technique was used to examine VEGF expression in the primary tu- mor tissue. The frequency of VEGF expression, which was associated with lower relapse-free survival rates, was found to be high (85.4%) in OC patients (p > 0.05).The tumor expression of the angiogenic factor VEGF was shown to provide prognostic information in early-stage ovarian epithelial cancer.